2015
DOI: 10.1017/s1867299x00004256
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment in the European Union: Lessons from a Research Project

Abstract: In this article, we present some major lessons drawn from a recently completed research project. Our research dealt with ex-ante evaluation, mainly impact assessment (IA). We shed new light on research questions about the control of bureaucracy, the role of IA in decision-making, economics and policy learning, and the narrative dimension of appraisal. We identify how our findings stand in relation to conventional arguments about these issues, and reflect on their normative implications. We finally reason on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…However, in the practical area, sometimes IA or RIA can be approached by political way, which can be described by interests, such as bargaining, entrenched commitments, and diverse stakeholder values and interests (Dunlop & Radaelli, 2015). This is far beyond the main intention of IA or RIA itself, where the main assessment is evidence-based.…”
Section: Impact Assessmentmentioning
confidence: 99%
“…However, in the practical area, sometimes IA or RIA can be approached by political way, which can be described by interests, such as bargaining, entrenched commitments, and diverse stakeholder values and interests (Dunlop & Radaelli, 2015). This is far beyond the main intention of IA or RIA itself, where the main assessment is evidence-based.…”
Section: Impact Assessmentmentioning
confidence: 99%
“…However, a report of the European Parliament (EP) and the European University Institute on evidence and analysis in EU policy making concluded that institutional systems have an inbuilt tendency to resist change [8,35,45]. One of the key problems of evidence-based policy making is bureaucratic inertia, which limits the potential to accept new developments and ideas [8,54]. Public administrators leading the policy making process can also influence outcomes by choosing among different theories or methods and by their attention to marginal or incremental facts and values [54,55].…”
Section: Evidence-based Policy Making In the Eumentioning
confidence: 99%
“…Both the EU and Australia already use this classical 'better governance' principle at home (Dunlop & Radaelli 2015;Kupiec 2015). Before adopting a new regulation or revising an existing legislation, the relevant regulatory body must conduct an impact assessment study of the new proposed rules to evaluate their potential impact on the targeted market, on the economy in general, on labour and the environment, and on the public budget.…”
Section: Going Beyond Tisa: Regulatory Disciplinary Arrangements and mentioning
confidence: 99%